Role of Fermatean Neutrosophic Sets in Determination of Career Planning - Mamoni Dhar (Winaya Inspirasi Nusantara Foundation, 2026)
Fermatean Neutrosophic sets that combine membership degrees of Pythagorean fuzzy sets and neutrosophic sets provide a more effective means of representing uncertainty, vagueness, and indeterminacy. These type of sets are commonly utilized across various disciplines which offers a structure for addressing intrinsic uncertainties that inherits in real life situations, for example, when making decisions about career options, pattern identification, work-life equilibrium and entrepreneurship. This study mainly examines Fermatean neutrosophic sets, the various distance measures of Fermatean neutrosophic sets and the associated properties. The characteristics of these features are also investigated. In a Fermatean neutrosophic environment, distance measures play a very important role. These are used extensively in pattern recognition, medical diagnosis and decision making. The literature on neutrosophic theory has offered a variety of distance measurements over time, each with specific benefits and drawbacks. The common metrics used are Hamming, Euclidean and Hausdroff distances which are calculated element wise across the sets. Taking into consideration of the existing ambiguities, a new distance metric is introduced here for dealing with Fermatean neutrosophic sets. This method provides more comprehensive and reliable possibilities which can be helpful for prospective candidates to assess complex career options. Decision-making is aided by an approach described here for both people and organizations. Furthermore, an application based on Fermatean neutrosophic sets is shown to demonstrate the method's functionality.